If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3.5x + 20 = 56 Reorder the terms: 20 + x + 3.5x = 56 Combine like terms: x + 3.5x = 4.5x 20 + 4.5x = 56 Solving 20 + 4.5x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 4.5x = 56 + -20 Combine like terms: 20 + -20 = 0 0 + 4.5x = 56 + -20 4.5x = 56 + -20 Combine like terms: 56 + -20 = 36 4.5x = 36 Divide each side by '4.5'. x = 8 Simplifying x = 8
| 9x-6x=8 | | 3(4y+2)+7y= | | 8x^2-2x+2=0 | | 6(u-9)-1=-5(-3u+8)-3u | | 5+(9+18-3)-3= | | 7(m+5)=22 | | 8-n=34 | | 7nsquared+7=12n | | 2(4x+3)+6= | | -56=88-9x | | 29-7x=28x-28 | | 9+14x+5x=180 | | 7-2f=1.98 | | 10-2y+4x=0 | | -7[4+7(-5+7)]+16= | | 50+3b=134 | | 3(1)=3 | | 7x+6=2z+2 | | 12x-13=-6x | | 6a-9-8a+5a= | | 5x+200=3x-300 | | -23n+13n+47-5n=-28 | | 3l+4-4l=-3 | | 53+18w=c | | 7x-4=37 | | 3(t-3)-2t=-30 | | (2m+3t)(3m-4t)= | | y=6000(1+0.04)5 | | 9x-8=8x+1 | | x^3-13x^2-2x+26=0 | | 7-3x-(-5x+2)+1+7x=5x | | 2x+4x-9x+7= |